Evaluation of Land Suitability for Sugar Cane Cultivation - Thariq Naufal Haq; Bakti Wisnu Widjajani; Siswanto Siswanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Land suitability is an important aspect in land planning and management, especially to determine the potential of land to support various agricultural and forestry activities. This study aims to evaluate the land suitability in the UPN Veteran East Java State Defense Garden located in Wonosalam District, Jombang Regency. The methodology used in this study involves the analysis of various factors such as soil texture, slope, soil type, rainfall, and water availability. Data were collected through field observations, soil sampling, and literature reviews related to soil physical and chemical characteristics. The evaluation results showed that most of the garden area has good suitability for certain agricultural activities, with some areas requiring special handling to optimize land use. The main factors affecting land suitability in this area include varying slope gradients and organic matter content in the soil. Recommendations from the results of this evaluation include better soil management, including the application of soil conservation techniques, and the selection of plant types that are appropriate to the characteristics of the land. This study is expected to provide useful information for garden planning and management to achieve optimal and sustainable productivity.